Lessons from a multidisciplinary partnership involving women parliamentarians to address the overuse of caesarean section in Italy. Issue 2 (23rd February 2020) - Montilla, Pilar; Merzagora, Francesca; Scolaro, Elisa; Requejo, Jennifer; Ricciardi, Walter; Meli, Elena; Bazzi, Adriana; Vittori, Giorgio; Bustreo, Flavia; Boldi, Rosanna; Rizzoti, Maria; Merialdi, Mario; et al.
Abstract : The increase of caesarean sections (CS) represents a global concern. Interventions tested to reduce unnecessary caesareans have shown limited success to date, partly because they have focused on medical perspectives or on single faceted interventions targeting only one group of stakeholders. Limited attention has been given to examining multidisciplinary and advocacy activities that could reduce unnecessary CS by raising awareness and engaging the media, advocacy groups, healthcare professionals and politicians. In 2009 in Italy, the national CS rate was the highest in Europe and momentum was building for action. This case study includes a description of the activities conducted in Italy during 2009–2012 by a partnership that included the non-governmental organisation Osservatorio Nazionale sulla Salute della Donna, a bipartisan group of Italian women parliamentarians and the WHO. The objectives were to generate awareness about the increase and overuse of CS in Italy, to foster political actions to reverse this trend, to engage with the media and journalists and to better understand women's birth preferences and needs. A reduction of the CS rate has been observed in Italy following the activities of the initiative from 38.4% in 2009 to 34.2% in 2015 according to the Ministry of Health. Although we cannot infer a casual association between the Partnership and the CS decrease, it did contribute to political momentum and specific actions that should, in theory, have contributed to this reduction. These include the engagement of women parliamentarians for policy change, improved understanding of the local drivers of increases of CS including women's needs and preferences, raising awareness and working with the media to convey appropriate information and an inclusive strategy giving the opportunity to local stakeholders to make their voices heard. This partnership initiative illustrates a model for generating dialogue, reflection and action in countries showing signs of readiness to address escalating CS.